Human Responses to Pandemics Then and Now: A Comparative Study of Giovanni Boccaccio's the Decameron and Emile St. John Mandel's Station Eleven - Sharma, Prakash; Upadhyay, Toya Nath (International Research Journal of MMC, 2024)
This research work makes a comparative study of Giovanni Boccaccio's The Decameron (1353) and Emile St. John Mandel's Station Eleven (2014) to investigate how they project human responses to pandemics over a time difference of almost seven centuries. The first fictional work belongs to the fourteenth century whereas the second to the twenty-first. The main aim of this study is to critically observe the differences, if any, in human responses to pandemics. Analyzing the texts, drawing on the critical ideas of Frank M. Snowden as a theoretical perspective and collecting data from scholarly publications, the study concludes that there are differences in the outward responses to pandemics but similarities in the basic motive. Human beings liked to flee away from the infected place due to the fear of insecurity there. The methods taken up to minimize the negative impacts of pandemics vary then and now. In the fourteenth century, human beings were religiously guided whereas in the twenty first, they are guided by science and technology. Similarly, in the representation of both pandemics, the role of art is valued greatly. Based on the qualitative research design, this research work obtains data from the library study and uses textual analysis method for data analysis in relation to the research problems. This research is valuable for the general public and the health researchers for developing protective measures in the context of the sudden outbreak of pandemics.